Improving the Students’ Speaking Ability Through the Use of Personal Experience - Dea Serly Safitri; Nurdin Noni; Maemuna Muhayyang (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
The objective of this research was to find out whether using personal experience improves students’ speaking ability. This research employed quantitative method with pre-experimental design. The population in this research consisted of second-year students at SMPN 26 Makassar, totaling 264 students across eight classes. The sample was selected using purposive sampling, focusing on class VIII-3, which had 28 students. This class was chosen based on two factors: preliminary observations indicating a need for fluency improvement, and its representativeness of the larger population. This research used SPSS as the tool for the data analysis. The findings reported that the use of personal experience contributed positively to the improvement of students’ speaking fluency at SMP Negeri 26 Makassar. This is reflected in the pre-test and post-test score comparison, which showed notable progress in fluency-related aspects, including smoother speech delivery, fewer hesitations, and more spontaneous verbal expression. Statistical analysis through a paired sample t-test revealed a significant difference between pre-test and post-test scores, while N-gain analysis indicated moderate improvement. These findings suggest that incorporating students’ personal experiences into speaking activities may be an effective way to enhance fluency in EFL classroom contexts. Keywords: Personal experience, Speaking ability, Students’ improvement